2021
DOI: 10.26434/chemrxiv.14739219
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Wildfire Smoke Impacts on Indoor Air Quality Assessed Using Crowdsourced Data in California

Abstract: <p>Wildfires have become the dominant source of particulate matter (PM<sub>2.5</sub>, < 2.5 µm diameter) leading to unhealthy air quality index occurrences in the western United States. Since people mainly shelter indoors during wildfire smoke events, the infiltration of wildfire PM<sub>2.5 </sub>into indoor environments is a key determinant of human exposure, and is potentially controllable with appropriate awareness, infrastructure investment, and public education. Using time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
32
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(36 citation statements)
references
References 31 publications
3
32
1
Order By: Relevance
“…7 Another study used publicly available data from the PurpleAir sensor network to measure PM 2.5 infiltration among 1400 buildings in California. 39 In contrast with our results, the authors found that particle infiltration to the indoor environment decreased during wildfire events compared with days not impacted by wildfires. However, even with reduced particle infiltration, mean indoor PM 2.5 concentrations were still nearly three times higher on wildfire days than on non-wildfire days.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…7 Another study used publicly available data from the PurpleAir sensor network to measure PM 2.5 infiltration among 1400 buildings in California. 39 In contrast with our results, the authors found that particle infiltration to the indoor environment decreased during wildfire events compared with days not impacted by wildfires. However, even with reduced particle infiltration, mean indoor PM 2.5 concentrations were still nearly three times higher on wildfire days than on non-wildfire days.…”
Section: Discussioncontrasting
confidence: 99%
“…Reisen et al measured indoor and outdoor air quality for 1 week at 21 residences and found that age and ventilation due to penetration points played a significant role in the infiltration of ambient PM 7 . Another study used publicly available data from the PurpleAir sensor network to measure PM 2.5 infiltration among 1400 buildings in California 39 . In contrast with our results, the authors found that particle infiltration to the indoor environment decreased during wildfire events compared with days not impacted by wildfires.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One approach to estimating infiltration of PM 2.5 of outdoor origin Finf$$ {F}_{inf} $$ is to apply a physical model, which is based on several known quantities: air change rate, penetration coefficient of outdoor PM 2.5 , and deposition rate of indoor PM 2.5 . This approach has been widely used in the literature 24‐27 . However, these parameters are difficult to obtain for a large number of different households and communities in a large‐scale study like ours.…”
Section: Resultsmentioning
confidence: 99%